The Effect of Perceived Organizational Support and Work Life Balance on Employee Job Loyalty at PT Alamjaya Wirasentosa - Luvia Mardana; Simanjorang, Feronica (Talenta Publisher, 2024)
Human resources are a supporting factor in achieving organizational goals and also the most valuable asset in the organization. Good human resource management will be advantageous to the business. Human resources have a very important role in the wheels of industry and organization because human resources are the main driving force for all resources in an industry and organization. This study's research methodology is quantitative research with an associative approach. Sampling was done through simple random sampling technique with 68 respondents as samples. The investigation's findings demonstrate that the variables of perceived organizational support and work life balance have a significant effect on employee job loyalty and all independent variables simultaneously affect employee job loyalty. The coefficient of determination test shows that there is a fairly close relationship between perceived organizational support and work life balance on employee work loyalty with an R value of 0.653. Through the adjusted R square value, it is also recognized that the variable between perceived organizational support and work life balance contributes 40.9%, to the remaining employee work loyalty variable of 59.1% which is influenced by other variables not discussed in this study.